A follow-up study of NSDB scholarship leavers, 1958-1976 - Aguila, Cynthia Bongat- 1950- (1979)
This study is a follow-up of the educational activities of the National Science Development Board Scholarship leavers for the period 1958-1976. The study focused on NSDB scholars who continued to pursue bachelor's degree programs at the University of the Philippines after leaving the scholarship program. The subjects are 322 NSDB scholarship leavers classified as either graduated or not graduated. It made use of the descriptive research method using documentary analysis. Based on the findings of the study, it was concluded that the scholarship leavers continue and complete undergraduate programs, leavers tend to pursue the same courses they were enrolled in at the time of scholarship award, leavers tend to perform academically poorer after leaving scholarship, and those who were in 4-year degree programs took proportionately longer time than those in 5-year degree programs.
"March, 1979."
Vita.
Thesis (M.A.T. : Chemistry)--University of the Philippines, Diliman.
Keywords: College students -- Scholarships, fellowships, etc -- Philippines; Scholars -- Philippines; Scholarships -- Philippines